Concomitant in Vivo Voltammetric and Electrophysiological Analysis Indicate that Nociceptin/Orphanin FQ Affects Dopamine and then Serotonin Activities in Brain Substancia Nigra. - Crespi Francesco (International Physiology Journal, 2019)
Nociceptin/orphanin-FQ (NOCI) together with its receptor NOP are widely expressed in cortical and subcortical motor areas and it is known that NOCI acts as an anxiolytic attenuating the behavioral inhibition of animals acutely exposed to stressful/anxiogenic conditions. Influence of NOCI upon the dopaminergic system has been observed in the ventral tegmental area and in the nucleus accumbens as well as an inhibitory action of NOCI is described upon serotoninergic mechanisms at cells and terminal levels. In particular, it is known that serotoninergic fibers from the raphe system project to the substancia nigra (SN) and that this modulation is behaviourally relevant. In the present work, the effect of exogenous NOCI injected into the SN upon DA and 5-HT levels have been analyzed by means of differential pulse voltammetry and nafion-carbon fiber microelectrodes. Electrophysiological monitoring of multicell activity was concomitantly performed with the same microsensor. It appeared that both levels of these biogenic amines were specularly altered, with possibly a driving influence of the DA activity upon the serotoninergic function(s).
Keywords: Nociceptin/orphanin-FQ